The relationship between health professionals perceptions of innovative work behavior and their metaverse knowledge and awareness levels - Duzcu, Tuba (BMC health services research, 2025)
Healthcare institutions have been affected by the changing environmental conditions with digitalization, and have turned to developing business models compatible with technological changes and adapting their institutions to these changes. For this change and adaptation, it is necessary to determine the innovative work behavior perception of healthcare professionals. This study aims to examine the relationship between healthcare professionals' innovative work behavior perceptions and metaverse knowledge and awareness levels together with demographic characteristics. In the study, a quantitative research method was applied using the Metaverse (MS) Scale and Innovative Work Behavior (IWB) Scale, and the subject was examined with structural equation modeling. An online questionnaire prepared via Google Forms was applied to 253 healthcare professionals university graduated residing in Istanbul who accepted to participate in the survey voluntarily through snowball sampling. The responses obtained from the participants in the study were analyzed with SPSS for Windows 29.0 and AMOS 25.0 package programs. Discriminant validity analysis was performed between the variables and it was investigated whether the separation between the variables was sufficient for structural equation modeling. The effect of demographic characteristics on the IWB scale and the effect of IWB scale sub-dimensions on the MS scale sub-dimensions were investigated. It was determined that the effect of IWB Scale sub-dimensions on MS Scale sub-dimensions was significant. The effects of the IWB Scale sub-dimensions "Opportunity Exploration" and "Idea Generation" on the MS Scale sub-dimensions "Technology, Digitalization, Social and Lifestyle" were found to be positive and significant. The effect of demographic characteristics such as "education, income, years of professional experience" on the sub-dimensions of the scales was found to be positive and significant. Today, it is an important requirement for healthcare professionals to have metaverse awareness and innovative work behavior perception. It is thought that it is important for healthcare managers and policy makers to measure these two levels of healthcare professionals and to include people with high levels of innovative work behavior perception and metaverse awareness in their institutions. In this study, healthcare professionals' perception of innovative work behavior increases or affects the level of metaverse knowledge.